The effect of intraoperative autofluorescence monitoring on unintentional parathyroid gland excision rates and postoperative PTH concentrations—a single-blind randomized-controlled trial - Papavramidis, Theodosios S.; Chorti, Angeliki; Tzikos, George; Anagnostis, Panagiotis; Pantelidis, Pantelis; Pliakos, Ioannis; Panidis, Stavros; Papaioannou, Maria; Bakkar, Sohail; Unal, Ethem; Michalopoulos, Antonios (Endocrine, 2021)
Purpose Intraoperative imaging of parathyroid glands (PGs) has been developed in order to reduce the risk of unintentional parathyroidectomy during total thyroidectomy. This novel modality is based on their intrinsic characteristic of autofluorescence (AF) after near-infrared light exposure. The aim of this study was to assess the effect of this method on the risk of unintentional PG excision (total or partial) during total thyroidectomy. Methods This was a single-blind, randomized-controlled trial including adult patients who underwent scheduled total thyroidectomy between December 2019 and March 2020. These patients were randomly allocated to two groups: one in which near-infrared autofluorescence imaging (NIRAF) was applied (NIR group) and one without NIRAF (NONIR group). Hormonal and biochemical assessment was performed pre- and 24-h postoperatively. AF findings and the number of PGs autotransplanted were recorded. Results One-hundred and eighty patients were eligible. Unintentional (total or partial) PG excision rates during total thyroidectomy in the NONIR ( n = 90) and NIR ( n = 90) groups were 28.9% [95% confidence interval (CI) 19.8–39.4%] and 14.4% (95% CI 7.7–22.1%), respectively ( p = 0.02). Furthermore, NIR reduced the risk of parathyroid tissue presence in the specimen sent for pathology (relative risk 0.51, 95% CI 0.28–0.92; p = 0.02). However, the number of PGs identified by NIR could not predict the risk of postoperative hypoparthyroidism. Conclusions NIRAF imaging during total thyroidectomy led to a significant reduction in PG excision rates. However, this modality did not result in the reduction of postoperative hypoparathyroidism or hypocalcemia risk.